Competitive adsorption of binary negatively charged proteins in egg white during foam evolution: From bulk solution to air-water interface. (July 2023) - Jin, Haobo; Pan, Jiajing; Zeng, Qi; Li, Zuyue; Jin, Yongguo; Sheng, Long
Abstract: The molecular properties, adsorption behavior and interfacial film structure of the binary protein system formed by ovalbumin and ovomucoid in egg white during foam initiation and stabilization were investigated. Electrostatic repulsion facilitated the dispersion of the binary protein in the bulk phase. Surface hydrophobicity and molecular flexibility were positively correlated with the proportion of ovomucoid, while surface charge density was negatively correlated with it. Tyrosine and phenylalanine tended to be in contact with the bulk phase, while tryptophan migrated toward air. Although the Kdiff was low for both ovalbumin (0.447 mN/m/s 1/2 ) and ovomucoid (0.472 mN/m/s 1/2 ), the mixed system facilitated the diffusion of the proteins. Interfacial dilatation rheology concluded that ovomucoid enhanced the solid-like character of the binary system, although film formed by a single ovomucoid (slope = 0.59) had the poorest mechanical properties, which relied on strong protein-protein interactions (slope > 1) at the interface. During foam stabilization, the binary protein at the natural ratio (5:1) exhibited the best macroscopic stability (94.1%), which might be related to the less pronounced Plateau drainage in the late stabilization phase. Pearson correlation analysis suggested that foam formation and stability were influenced by multiple factors, and that an optimal balance between positive and negative factors was the key to obtaining desirable foam properties. This study would provide a new insight to understand the interfacial adsorption and film-forming behavior of negatively charged proteins and the directional regulation of egg white foam properties. Graphical abstract: Image 1 Highlights: Electrostatic repulsion dominated the interactions between ovalbumin and ovomucoid. Protein conformational changes occurred throughout the foam evolution. Synergy existed in the competitive adsorption of ovalbumin and ovomucoid. Binary proteins favored interfacial adsorption and film strength over single ones. Foam properties were determined by a combination of positive and negative factors.